A Case of Acute Fatty Liver of Pregnancy - Ülger, Fatma; Çelik, Handan; Dilek, Ahmet; Tosun, Migraci; Altunsoy, Süleyman; Malatyalıoğlu, Erdal; Şahinoğlu, Haydar (Gynecology Obstetrics & Reproductive Medicine, 2009)
We described a case of acute fatty liver developed early postpartum period. Acute fatty liver of pregnancy (AFLP) is a rare medical condition and is important due to its implications on maternal and fetal morbidity and mortality. AFLP is managed with supportive care and close surveillance is needed in these patients. We report the case of a previously healthy 29 year old woman within the postpartum first day who presented to the emergency department with postpartum severe vaginal bleeding. An evaluation revealed hepatic and renal failure. The patient required aggressive supportive care, transfusion of multiple blood products in intensive care unit. This case was unusual because AFLP was reported in postpartum period and the patient presented due to postpartum severe vaginal bleeding after vaginal delivery and was subsequently diagnosed as AFLP